Multicenter Study on the Clinical Characteristics, Diagnosis, and Treatment Outcomes of Insulinoma: Insights From 15 Medical Centres - Topsakal, Senay; Yaylali, Guezin Fidan; Yarar, Zeliha; Merdin, Fatma Avci; Karsli, Seda; Ciftci, Sema; Yarman, Sema (Wiley, 2025)
ObjectiveThis study aimed to evaluate the clinical characteristics, diagnostic approaches, and treatment outcomes of insulinoma patients from diverse regions across the country. We conducted a retrospective analysis of medical records from 76 adult patients diagnosed with insulinoma between 2018 and 2023 at 15 medical centres. Data collected included demographics, presenting symptoms, laboratory and imaging results, surgical reports, pathology findings, and clinical follow-up information. DesignMulti-centre retrospective study. MethodsThe study revealed that key factors such as age, BMI, symptom duration, tumour size, and follow-up period were similar across genders. The majority of patients experienced neuroglycopenic symptoms, particularly during fasting. Insulinoma was typically diagnosed either during fasting or spontaneously, with no significant gender differences in glucose and insulin levels during hypoglycemia. However, men exhibited higher C-peptide levels (p < 0.05). Common comorbidities included hypertension, hypothyroidism, and cardiovascular conditions, and some patients had been using antiepileptics or antidepressants before their diagnosis. ResultsPreoperative tumour diagnoses were largely accurate, with endoscopic ultrasound (EUS) being the most effective method. Most tumours were small ( < 2 cm) and located in the pancreas body, with the majority being solitary. Surgical treatments primarily involved enucleation or distal pancreatectomy. Follow-up data indicated high remission rates, with low rates of nonremission and mortality. ConclusionThis study emphasises that early diagnosis and intervention, particularly in patients with a history of neurological or psychiatric issues, postprandial symptoms, or rapid symptom improvement after treatment, can lead to significantly better outcomes.
Keywords: anthropometric parameters; comorbidities; insulinoma; mortality; prognosis; treatment modalities; tumour behaviour